Análisis para la factibilidad de la puesta en servicio de Sistemas de Medición Avanzada para Clientes ubicados en la Comunidad de Patután de la Empresa Eléctrica Provincial Cotopaxi S.A. - Aimacaña Quishpe, Sixto Fidel (2022)
The research project seeks to get the feasibility analysis for advanced measurement systems commissioning, said system will allow to make: readings, cuts, and reconnections of a remote way, at reducing the operating expenses; that these tasks entail, which are analyzed and quantified all the necessary resources their implementation, through a operational variables parametric analysis, network conditions, existing meters, which have been validated by the information gathering into field and provided data for the distribution enterprise, resulting in a total of 680 clients, of which 3.68% have 1 phase-2 wire meters and 96.32% have 2 fhase-3 wire meters. As well as characterizing and conceptualizing the most relevant benefits, which the systems AMI implementation would offer to the participants, enterprise-consumer. Besides, it is determined the communication topology type to be implemented in the concession area, which covers coverage radii of 350 to 450m due to its geographical condition. In the same way, it is identified the equipment location points, such as data concentrators and signal repeaters that allow communication without information loss from energy meters, which in this case is proposed by the active energy meter and demand with RF. For what the communication process between the more accurate and reliable devices were used the free software Radio Mobile, which it could was possible created link points of the meter’s furthest from concession area, thus, being able to show that the proposed communication topology, in this case a Netting network and via Radio Frequency communication, it is recommended. Finally, it is made an economic and financial analysis about the project viability based to the variables and benefits that would assume the advanced measurement technology installation, by which it is determined the feasibility of same, with an TIR greater than the interest rate, in this case at 31% and a VAN greater than zero, that is, USD 223,355.14, thus, it is complying with the main aim of present research project.